Anti-inflammatory Property of Galectin-1 in a Murine Model of Allergic Airway Inflammation - Yunxiang Lv; Mengyuan Dai; Muzi Wang; Fangfang Chen; Rongyu Liu (Journal of Immunology Research)
Galectin-1 (Gal-1) has immunomodulatory activities in various allergic inflammatory disorders, but its potential anti-inflammatory properties on allergic airway diseases have not been confirmed. We explored the pharmacological effects of Gal-1 on the progression of allergic airway inflammation and investigated the underlying mechanism. Female C57BL/6 mice were sensitized on day 0 and challenged with ovalbumin (OVA) on days 14-17 to establish an allergic airway inflammation model. In the challenge phase, a subset of mice was treated intraperitoneally with recombinant Gal-1 (rGal-1) or dexamethasone (Dex). We found that rGal-1 inhibited pulmonary inflammatory cell recruitment, mucus secretion, bronchoalveolar lavage fluid (BALF) inflammatory cell infiltration, and cytokine production. The treatment also suppressed the infiltration of eosinophils into the allergic lung as indicated by decreased expression levels of eotaxin and eosinophil peroxidase (EPX). However, only the expression levels of IL-25, neither IL-33 nor TSLP, were significantly decreased in the lung by rGal-1 treatment. These immunomodulatory effects in the allergic lung were correlated with the activation of extracellular signal-regulated kinase (ERK) signaling pathway and downregulation of endogenous Gal-1. In addition, rGal-1 reduced the plasma concentrations of anti-OVA immunoglobulin E (IgE) and IL-17. Our findings suggest that rGal-1 is an effective therapy for allergic airway inflammation in a murine model and may be a potential pharmacological target for allergic airway inflammatory diseases.